Comparative Performance of Rough R and Smooth S Colonies of Acetobacter aceti CRF 3 for Acetic Acid Production - Thiripurasundari, G (International Journal of Pharmaceutical & Biological Archive, 2013)
Comparative Performance of Rough R and Smooth S Colonies of Acetobacter aceti CRF 3 for Acetic Acid Production